Perbedaan Konsumsi Minuman Bersoda dan Isotonik Terhadap Peningkatan Plak Gigi Mahasiswa Fakultas Kedokteran Gigi Universitas Muhammadiyah Surakarta Angkatan 2014 - Mulyanti, Riska, drg. Edi Karyadi, M.M, drg. SE Yuletnawati, MDSc (2015)
Carbonated drink and isotonic drinks are beverages that are very favored by the people especially teenagers. Increased consumption of Carbonated drink and isotonic drink could adversely affect dental health. Soft drinks are beverages contain carbonated, carbohydrates, calories, acid, and dyes. Isotonic drinks are beverages that can restore stamina, because isotonic contain carbohydrates, acids, and minerals. This study aims to determine the effect of the difference between carbonated drinks and isotonic to the improvement of dental plaque on Students of Dentistry, University of Muhammadiyah Surakarta, force in 2014. This type of research is a quasi-experimental study with pretest and posttest design. The study population was a student at the Faculty of Dentistry, University of Muhammadiyah Surakarta. The sample used in this study were students of Dentistry UMS force 2014 numbered 52 students. Data were analyzed was performed with SPSS 21.0 to test the independent sample t-test and with a significance level of 95%. T-test results showed that there were significant differences between carbonated drinks and isotonic with the results obtained by t-test analysis of dental plaque soft drinks 9.89 and 6.21 dental plaque of isotonic drinks. These results indicate a significant difference. So the conclusions are that dental plaque consume carbonated drinks have a higher capacity than the increase plaque consume isotonic drinks.